Bentuk Kebahasaan Ungkapan Makian Dalam Drama Great Teacher Onizuka - Mochammad Fredy; Eva Amalijah; Luluk Ulfa Hasanah (Mezurashii: Journal of Japanese Studies, 2022)
Language is created to maintain good relations between people, also to avoid misunderstandings. However, the environment can trigger a change in emotion which is then making someone expressed their feelings in the form of swear words. Swearing aims to express displeasure, hatred, dissatisfaction, exclamation, or even intimacy. Japanese people who are known as people with good values and ethics, are sometimes forced to say such as harsh words to vent their feelings through swear words, named nonoshiri hyougen. The Japanese movie drama Great Teacher Onizuka by Kazuhisa Imai is the object of this research. The research is conducted in a qualitative descriptive approach, which focused on analyzing the use of swearing expressions based on the classification of language forms. The result is that swear words in the form of clauses are not found. Otherwise, swear words in the form of words and phrases are found in the Japanese movie drama Great Teacher Onizuka. Keywords: Language, Swear word, Language forms